2011
DOI: 10.1021/ol2005903
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Trifluoromethylation of Aryl and Vinyl Boronic Acids with An Electrophilic Trifluoromethylating Reagent

Abstract: A copper-catalyzed trifluoromethylation of aryl- and alkenylboronic acids with Togni's reagent was described. The reaction proceeded in good to excellent yields for a range of different substrates including heteroarylboronic acids and substrates with a variety of functional groups under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
92
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(103 citation statements)
references
References 46 publications
3
92
0
8
Order By: Relevance
“…[4][5][6][7][8][9] Several years ago, Togni and co-workers 10 reported a conceptually new family of formally electrophilic CF 3 transfer reagents based on a cyclic hypervalent iodine(III) core, the most successful ones being Togni's reagents 1 and 2 (Scheme 1). These reagents are employed in the trifluoromethylation of phosphorus-, carbon-and oxygen-centered nucleophiles such as phosphines, 11 α-nitro-and β-keto-esters, 12,13 phosphorothioates, 14 aromatics, 15 alcohols, 16 sulfonic acids, 17 hydrogen phosphates, 18 aldehydes, 19 phenols, 20 arylboronic acids, 21 and quinones 22 . …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Several years ago, Togni and co-workers 10 reported a conceptually new family of formally electrophilic CF 3 transfer reagents based on a cyclic hypervalent iodine(III) core, the most successful ones being Togni's reagents 1 and 2 (Scheme 1). These reagents are employed in the trifluoromethylation of phosphorus-, carbon-and oxygen-centered nucleophiles such as phosphines, 11 α-nitro-and β-keto-esters, 12,13 phosphorothioates, 14 aromatics, 15 alcohols, 16 sulfonic acids, 17 hydrogen phosphates, 18 aldehydes, 19 phenols, 20 arylboronic acids, 21 and quinones 22 . …”
Section: Introductionmentioning
confidence: 99%
“…Most current processes for accessing CF 3 containing molecules are performed by carboxy or trichloromethyl group substitution using hazardous fluorinating reagents under harsh reaction conditions 6 . Cross-coupling reactions between organohalides [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] or boronic acids (or their esters) [25][26][27][28][29][30][31][32][33][34] and trifluoromethylating reagents are another common approach. Although CF 3 groups can be regioselectively introduced to aromatic rings in cross-coupling reactions, requirement of multiple steps for the preparation of aryl halides and boronic acids/esters and generation of stoichiometric amounts of metal salts decrease synthetic efficiency.…”
mentioning
confidence: 99%
“…In 2011, Xu et al 61 and Liu et al 62 reported two similar methods for trifluoromethylation of aryl boronic acids (Figure 28). Umemoto and Togni reagents were used as electrophilic CF 3 sources.…”
mentioning
confidence: 99%